MITIGATION AND LANDSLIDE HANDLING AT MAIN ROAD STA 21+700 BOGOR-CIAWI-SUKABUMI TOLL SECTION 2 DURING THE CONSTRUCTION PERIOD - Edward, Marsesa
Landslides are one of the natural events that often occur in Indonesia and as we know, these disasters can cause material and non-material losses to society. Construction of the Bogor - Ciawi - Sukabumi toll road Section 2 located in Ciawi, West Java, with a length of 15.4 kilometers (km). Section 2 completes the gate to gate of IC Cigombong – IC Cibadak. The exact location being reviewed, namely STA 21+700, has high embankment work on the Main Road. Based on the condition of the land in the field, there is insufficient land acquisition to meet the slope of the embankment 1.4. the location which also borders the river is another factor in the field. In this study, analyzing the mechanism of the failure of the high embankment. In analyzing the sliding mechanism, the condition of subgrade material, embankment soil material condition and the influence of rain intensity are considered. The condition of the subgrade and the condition of the embankment soil is obtained from the results of the soil investigation. The author uses primary data to obtain the actual condition of the land at the location. From the existing primary data then compared and analyzed against data from the previous planning. Slope stability analysis was carried out numerically using software based on the finite element method. Use of the 2D Plaxis Program to include modeling of existing conditions and find solutions for repairing landslides that occurr. From the results of the analysis, it is known that the landslide occurred because the existing CCSP did not intersect the original landslide line. The results were obtained after the landslide with Safety Factor (SF) < 1. Then in getting a solution for handling the slide, a re-loading model was carried out and the option was using 3 Soldier Pile traps so that it could cut the landslide area and increase the Safety factor (SF) to > 1.4. The solutions presented in this paper are also related to field implementation methods to ensure the expected quality and implementation time. The mechanism of slope failure due to rain at the location under review can be identified. The results of this study can be used in similar cases in road embankment Construction.